RETRACTED: Young pine stands growth on abandoned farmlands - Vais Andrey; Popova Valentina; Andronova Alina; Zaykova Polina; Mamedova Sevinch; Chanchikova Svetlana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001